Análise do DNA barcode de espécies dos clados Scinax ruber e Scinax catharinae (Anura, Hylidae) do sudeste brasileiro - Granato Neto, Elias (2016)
As amphibians in general have suffered a strong population decline, it is extremely necessary to know its biodiversity for creating more efficient handling strategies. Brazil has the largest species richness of these animals, however with few studies compared to this great biodiversity. Among the amphibians the Scinax genus (Anura, Hylidae), presents a puzzling taxonomic history and a large number of species, some of them considered species complex. In this paper we characterized the DNA barcode of some species of two clades of the genus - S. catharinae and S. ruber and the haplotypes of the species with the highest number of samples – S. fuscovarius and S. perereca. For S. fuscovarius we found 21 haplotypes and for S. perereca 7 haplotypes. We brought up the possibility of a species complex within S. perereca, being found a high genetic and haplotype diversity among individuals living in sympatry. Also we detected the same haplotype shared by specimes of S. fuscovarius as far as 700 km and we characterized the first COI region of S. longilineus, S. perereca, S. skaios and S. x-signatus, which will help in future studies of molecular taxonomy.